Efeitos da radiação ionizante em nanopartículas magnéticas de óxido de ferro - Schmude, Angelika Von (2021)
In this work, the effects of X-rays, gamma rays, and proton beams on the structure and properties of magnetic iron oxide nanoparticles were investigated. The preservation of the physical-chemical properties of these nanostructures when subjected to ionizing radiation is extremely important for applications in the biomedical area, in view of their potential application in new oncological technologies such as the MR-Linac. The samples used were commercial and home-made iron oxide nanoparticles synthesized using the coprecipitation method and the polyol route and prepared in different forms (film on silicon, composite tablets, and aqueous suspension). The equipments used for the irradiation of the samples were a Clinac IX linear accelerator from Varian of 6 MV, a cobalt-60 pump and a 3 MV Tandetron ion implanter (2 MeV H+ beam). The delivered doses varied between 10 and 720 Gy in the case of photon irradiations. The results indicate a slight decrease of the saturation magnetization after exposure to high doses. Images obtained by transmission electron microscopy do not show changes in the morphology of the nanostructures. Analyzes by X-ray diffraction show a reduction in crystallinity with increasing dose for the commercial NPs. The measurements of nuclear magnetic relaxation performed on the nanoparticles synthesized with dextran coating demonstrated an increase in the time of transversal relaxation (T2) with the increasing dose, possibly due to defects created during the irradiation process. Although it has not yet been possible to establish a clear quantitative dose-effect relation in the irradiated nanoparticles, it is clear that significant changes occur only at doses much higher than those used in the clinics.